1997
DOI: 10.1128/iai.65.10.4114-4121.1997
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of the C3 component of complement by peritoneal cells cultured with encapsulated Cryptococcus neoformans

Abstract: Two isolates of Cryptococcus neoformans were identified as being widely divergent in pathogenic potential after intratracheal infection of mice. These isolates differed in their ability to upregulate capsule synthesis when grown under tissue culture conditions, and this property correlated with virulence. We postulated that differential capsule synthesis may cause differential stimulation of macrophages to produce products such as complement components. To test this hypothesis, heat-killed yeast cells were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
0
24
2
Order By: Relevance
“…In those studies the effects of GXM evolved in the absence of serum and were therefore independent of complement activation. However, as several data indicate that GXM presumably activates the complement system [12,[54][55][56], the resulting generation of the chemoattracting factor C5a in the bloodstream might be an additional mechanism underlying the observed interference with leucocyte migration. The presence of massive amounts of C5a in the bloodstream would theoretically prevent neutrophils from responding properly to other chemoattracting substances present in the inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In those studies the effects of GXM evolved in the absence of serum and were therefore independent of complement activation. However, as several data indicate that GXM presumably activates the complement system [12,[54][55][56], the resulting generation of the chemoattracting factor C5a in the bloodstream might be an additional mechanism underlying the observed interference with leucocyte migration. The presence of massive amounts of C5a in the bloodstream would theoretically prevent neutrophils from responding properly to other chemoattracting substances present in the inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of massive amounts of C5a in the bloodstream would theoretically prevent neutrophils from responding properly to other chemoattracting substances present in the inflamed tissues. Although whole, encapsulated cryptococci clearly induce complement activation [13,[57][58][59], the ability of purified GXM to activate complement has not been unambiguously demonstrated [12,60], and data on GXMrelated C5a generation are currently not available. Evidence Figure 5 Effect of GXM treatment on myocardial infarct size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GXM was identified as the stimulatory substance to induce the production of C3 in peritoneal cells. 116 The complement receptors CR1, CR3 and CR4 are the main effector molecules to mediate binding and phagocytosis of cryptococci, as demonstrated by monoclonal antibodies against the three receptors that block binding of the yeast cells. 117,118 A ranking for the CRs demonstrates the dominance of CR3.…”
Section: Complement-mediated Effector Mechanisms In Cryptococcal Infementioning
confidence: 99%
“…It has been suggested that the pathogenicity of a particular C. neoformans isolate is dictated by the quantitative expression of its combined virulence traits, including the ability to grow at 37 ‡C, production of polysaccharide capsule and melanin [3]. Cryptococcal capsule synthesis is upregulated in some C. neoformans strains when grown in low iron medium (LIM) and under tissue culture conditions [4,5]. One such well-characterised strain is C. neoformans var.…”
Section: Introductionmentioning
confidence: 99%